Würde eine unabhängige europäische Wettbewerbsbehörde eine bessere Wettbewerbspolitik machen? - Oliver Budzinski (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2012)
– This chapter discusses the independence of competition authorities and addresses the question whether an independent European competition authority would perform a better competition policy than the competition office of the European Commission, which is not independent but, instead, integral part of the European government. After summarizing the main general considerations, the chapter defines better competition policy simplifying as avoiding or solving three selected problems of contemporary European competition policy. It finds that two of these three problems are indeed likely to be not existent with an independent competition agency whereas the third problem is not likely to be better solvable by an independent body. Eventually, the chapter addresses a recent proposal to implement an independent Council of European Competition Advisors (CECA) that monitors and evaluates the performance of the European Commission's competition division.
Keywords: 330